(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This research was conducted to study the hypoglycemic activity of C. chinesis Lam on type 1 diabetic disease and investigate the molecular and histological mechanism of its action .many parameters was investigated , Fasting blood glucose (FBG), Fasting serum insulin,Hepatic Insulin Gene Expression, pancreas Insulin Gene Expression ,Hepatic Insulin Receptors Gene expression and histological sections of pancrease and liver.54 Rattus rattus male rats weighting(180 -200g) were divided into 3 groups: A normal control daily administrated with Dw, B Diabetic control daily administrated with Dw and C diabetic group daily administrated with 400 mg/Kg body weight of C. chinesis Lam. methanolic extract, each group consisted of 18 rats and further divided into (3) sub- groups 1 ,2 and 3. According to the period of administration 30, 60 and 90 days respectively. The results showing the daily administration of 400 mg/Kg body weight of C. chinesis Lam. methanolic extract for 60 day causing significance decrease in FBG and In the other hand each of fasting serum insulin, hepatic Insulin gene expression,pancreas Insulin gene expression and hepatic Insulin receptor gene expression was increased in group C in compare to B group and return all studied parameters involving pancrease and liver texture to the normal state ,which were statically morphologically not appeared any significant difference from A group .this study concluded that the daily administration type 1 diabetic rats with 400 mg/Kg body weight of C. chinesis Lam. extract for 60 day was return fasting serum insulin and FBG to normal value by upregulated the gene expression of hepatic INS Gene ,INSR gene , pancreas INS Gene ,regenerate pancreatic beta- cell and returnthe texture of both liver and pancrease to the normal state